2019
DOI: 10.1007/s11615-019-00211-8
|View full text |Cite
|
Sign up to set email alerts
|

Warum initiieren Minister Evaluationen? Eine Fallstudie der flämischen Regierung in Belgien

Abstract: Policy evaluations can be set up for multiple purposes including accountability, policy learning and policy planning. The question is, however, how these purposes square with politics itself. To date, there is little knowledge on how government ministers present the rationale of evaluations. This article is the first to provide a diachronic study of discourse about evaluation purposes and encompass a wide range of policy fields. We present an analysis of evaluation announcements in so-called ministerial policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Further drawing on this typology, and as propagated in Howlett and Shivakoti (2014), the evaluation tools can be conceived as cases of authoritative policy instruments. Authority implies that governing bodies of the public sector, such as government agencies or parliaments, possess the power to demand evaluations (Bundi 2016;Pattyn et al 2019;Bali and Halpin 2021). They mandate certain procedural requirements in the policy-making process, to ensure that policies pass the test of effectiveness, efficiency, or other evaluation criteria often stipulated in law or regulations.…”
Section: Evaluation Tools With Agenda-setting Potential: Classificati...mentioning
confidence: 99%
“…Further drawing on this typology, and as propagated in Howlett and Shivakoti (2014), the evaluation tools can be conceived as cases of authoritative policy instruments. Authority implies that governing bodies of the public sector, such as government agencies or parliaments, possess the power to demand evaluations (Bundi 2016;Pattyn et al 2019;Bali and Halpin 2021). They mandate certain procedural requirements in the policy-making process, to ensure that policies pass the test of effectiveness, efficiency, or other evaluation criteria often stipulated in law or regulations.…”
Section: Evaluation Tools With Agenda-setting Potential: Classificati...mentioning
confidence: 99%
“…On paper, and as outlined above, policy evaluation has some overarching purposes that make it a useful instrument for governance procedures: fostering public accountability, promoting policy learning for the betterment of public action and facilitating future policy planning. However, the political and administrative appropriations of evaluations are much more complex than that in reality (Pattyn et al, 2019).…”
Section: Evaluation At the Heart Of Policy Strugglesmentioning
confidence: 99%
“…But actors with an interest in evaluation may also be constrained by their substantive policy field, as Pattyn et al (2019) demonstrate in the case of Flanders in Belgium. Some policy fields, such as the environment or mobility and public works, drew a large number of demands for evaluations by ministers.…”
Section: Evaluation Actors and Interests: Their Evolving Role And Infmentioning
confidence: 99%
“…The contributions to this special issue identified several ways in which the purposes and uses of evaluation intertwine with politics. In the case of Flanders in Belgium, Pattyn et al (2019) analysed to what extent government ministers focused on policy planning, accountability, and policy learning in their evaluation announcements and found that about one-third of the evaluations were orientated towards policy planning, two-thirds towards learning, and only a small number towards accountability. Therefore, the professed claims that new public management reforms generate greater accountability do not appear to be true in this case, although a focus on learning and policy improvement can point to potentially positive impacts of evaluation.…”
Section: Evaluation Purpose and Use: The Strategies Of Political Actorsmentioning
confidence: 99%